IMPLEMENTATION OF THE MOBILE-BASED DENTALK APPLICATION AS A MEDIA FOR INCREASING PUBLIC KNOWLEDGE IN USING THE TELEDENTISTRY APPLICATION - Sari Aldilawati; Amanah Pertiwisari; Andi Muhammad Irfan M.Amir (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Background: Teledentistry is defined as a method of using virtual conferencing technology to provide convenient diagnostics for remote care. The biggest challenge in the development of teledentistry is the understanding and knowledge of the public to use the service. Dentalk is an application designed as part of teledentistry that can provide easy access to dental health services, such as diagnosis, action plan, consultation, and follow-up. Material and Method: The type of research used is quasi-experimental research with pre-test and post-test group design. Questionnaires were made to measure the sample's knowledge in using the teledenstistry application, in this case the dentalk application. The research sample is a subject taken from a population that meets the research criteria, namely 40 samples. Result and Discussion: Based on the results of the comparison test, the value of 0.000 < alpha 0.05 means that there are differences in knowledge before and after using the dentalk application respondent. Conclusion: The paired sample t-test results can be concluded that there is an increase in knowledge in using the dentalk application.